The mediating role of total quality management between entrepreneurial orientation and SMEs export performance - Imran, Muhammad; Aziz, Azelin; Abdul Hamid, Siti Norasyikin; Shabbir, Muhammad Salman; Salman, Rabia; Jian, Zhaoquan (Growing Science Ltd., 2018)
The purpose of this study was to investigate the mediating role of total quality management (TQM) between entrepreneurial orientation (EO) and SME export performance in the manufacturing sector of Pakistan. This study was originated from the fact that only a few studies have examined on how the firm’s intangible resources and capabilities such as EO and TQM drive SMEs’ export performance. Some questionnaires in Likert scale were used to collect the data and 364 usable responses were received from the owner/managers of exporting SMEs. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used for the data analysis. The findings reveal significant relationship between EO and TQM with SME export performance. Furthermore, this study found the complementary mediating role of TQM between EO and SME export performance of manufacturing sector of Pakistan. This study has implications for owner/managers of SMEs. The results offer a better understanding regarding EO and TQM implementation to SMEs owner / managers. Thus, owner/managers of SMEs can take better decisions for the implementation of TQM practices. Furthermore, to the best of researcher’s knowledge, this study is the first work, which examines Pakistan`s SMEs export performance in association with the TQM as the mediating factor between EO and SME export performance.